Existence and Uniqueness of Positive Solutions for a System of Multi-Order Fractional Differential Equations (Communications in Mathematical Research, 2021)
In this paper, we prove the existence and uniqueness of positive solutionsfor a system of multi-order fractional differential equations. The system is used torepresent constitutive relation for viscoelastic model of fractional differential equations. Our results are based on the fixed point theorems of increasing operator andthe cone theory, some illustrative examples are also presented.
Keywords: fractional differential equation; Caputo fractional derivative; fixed point theorem; positive solution.